Theoretical Conceptualization of Local Budgets - М. V. Dubyna (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The transparence of budgets, corruption and control over the execution of local budgets in Ukraine has been increasingly in focus of international financial organizations in view of Eurointegration processes taking place in Ukraine. The significance of local budgets as a component of local finances has to be enhances, as the financial capacities of local self- governance bodies are conditional on local budgets. The article’s objective is to analyze theoretical grounds of local budgets as the principal component of local finances, and to build their conceptual framework. A review of the concepts “local finances” and “local budget” is made, the peculiarities of local finances are highlighted; the factors determining the impact of local finances on the socio-economic development of territories are outlined. The conceptual framework of local budgets is built, specifying their goal, functions and principles, administering bodies, objectives and purposes etc. in the conditions of decentralization. The review of interpretations of the local budget, including its economic meaning, allowed for giving the local budget definitions in the legal, material and economic dimension.